Diagnostic Accuracy of Bronchoscopy Procedures: Definitions, Pearls, and Pitfalls. Issue 4 (31st October 2022) - Gonzalez, Anne V.; Ost, David E.; Shojaee, Samira
Abstract : The field of diagnostic bronchoscopy has developed at an accelerated pace. Certain limitations have plagued the evaluation of advanced bronchoscopy techniques, including the use of inconsistently defined measures of diagnostic accuracy, and confusion around the definition of "diagnostic yield." This methodological review outlines standard measures of diagnostic accuracy and highlights how these differ from "diagnostic yield." We draw examples from the interventional bronchoscopy literature to illustrate key concepts and potential pitfalls.